A common maturation pathway for small nucleolar RNAs. - Terns, M P (1995)
We have shown that precursors of U3, U8 and U14 small nucleolar RNAs (snoRNAs) are not exported to the cytoplasm after injection into Xenopus oocyte nuclei but are selectively retained and matured in the nucleus, where they function in pre-rRNA processing. Our results demonstrate that Box D, a conserved sequence element found in these and most other snoRNAs, plays a key role in their nuclear retention, 5' cap hypermethylation and stability. Retention of U3 and U8 RNAs in the nucleus is saturable and relies on one or more common factors. Hypermethylation of the 5' caps of U3 RNA occurs efficiently in oocyte nuclear extracts lacking nucleoli, suggesting that precursor snoRNAs are matured in the nucleoplasm before they are localized to the nucleolus. Surprisingly, m7G-capped precursors of spliceosomal small nuclear RNAs (snRNAs) such as pre-U1 and U2, can be hypermethylated in nuclei if the RNAs are complexed with Sm proteins. This raises the possibility that a single nuclear hypermethylase activity may act on both nucleolar and spliceosomal snRNPs.